An outdoor environment of the historic fishing village of Kuala Sepetang / Muhammad Zamree Amran and Ana Kashfi Muhamad - Amran, Muhammad Zamree; Muhamad, Ana Kashfi (2019)
Kuala Sepetang is a thriving fishing village in the north-west of Taiping. Used to be called as Port Weld, this small town is once a busy transit point to transport tin to Taiping. This paper unfolds the outdoor environment based on end-user’s valuation using basic imageability and responsive environments analysis. Findings show that this historical fishing village has a distinct character that can be further exploited, subsequently improve the economy of this place.